2000
DOI: 10.1136/jms.7.2.97
|View full text |Cite
|
Sign up to set email alerts
|

Faecal occult blood screening for colorectal cancer at Nottingham: details of the verification process

Abstract: Cause specific mortality statistics derived from death certificates are highly dependent upon the accuracy of certification by the attending physician. In the Nottingham colorectal cancer screening trial, there were 12 624 deaths among the screening group and 12 515 among the control group during the period under consideration. There was no significant diVerence in all cause mortality rate (excluding deaths due to colorectal cancer) between the two study groups (rate ratio = 1.01, 95% confidence interval = 0.9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2010
2010
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…To our knowledge, only two previous analyses have examined the impact of mortality review on the results of randomized trials of cancer screening [2,4]. The first considered data from the four randomized trials of mammography screening conducted in Sweden [4].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To our knowledge, only two previous analyses have examined the impact of mortality review on the results of randomized trials of cancer screening [2,4]. The first considered data from the four randomized trials of mammography screening conducted in Sweden [4].…”
Section: Discussionmentioning
confidence: 99%
“…Also similar to our findings, in all but one instance in the Swedish trials mortality review tended to result in a larger estimate of the benefit of screening, and further there was one instance where the statistical significance of the results differed based on whether mortality review or death certificates were used to define endpoint. The second analysis considered data from the Nottingham trial of FOBT [2]. Death review in this trial was conducted for all deaths among known cases of colorectal cancer, as well as for those deaths for which colorectal cancer or carcinomatosis (with primary unspecified) was noted on the death certificate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CRC mortality rates were calculated from the underlying cause as stated on the death certificate and the verified cause of death after case note review 6. The verification process was blind to whether the patient was in the control or intervention arm, although in around 5% of cases it was apparent from the notes that the patient had been screened.…”
Section: Methodsmentioning
confidence: 99%
“…UCD as certified by the attending doctor was the basis of mortality classification, with one modification. At an earlier stage of the trial, independent assessors had reviewed case notes for all deaths where CRC or an unspecified primary tumour appeared to be a cause 11. Disagreements between certified causes and those verified by the assessors were evident, and it was concluded that certification under-reported certain or probable deaths from CRC.…”
Section: Methodsmentioning
confidence: 99%